APPLYING GEOGRAPHICAL INFORMATION SYSTEMS IN WETLAND MANAGEMENT IN THE BALATON-HIGHLANDS NATIONAL PARK (Hungarian Journal of Industry and Chemistry, 2000)
The Pécsely-basin is situated in the Balaton-Highlands National Park, which was founded in 1997. The basin is rich in wetlands increasing landscape diversity and the aesthetic value of this area. This paper gives a review on how different information sources, especially remote sensing can be used for inventorying wetlands. By using GIS, our basic intention was to establish a digitised inventory and database, which can serve in the future as a basis of any nature conservation work. In addition, we have investigated what information different layers might provide in wetland management and how it can be interpreted.
Keywords: wetland inventory; wetland management; Geographical Information Systems